Further evidence for early lunar magnetism from troctolite 76535. Issue 1 (4th January 2017) - Garrick‐Bethell, Ian; Weiss, Benjamin P.; Shuster, David L.; Tikoo, Sonia M.; Tremblay, Marissa M.
Abstract: The earliest history of the lunar dynamo is largely unknown and has important implications for the thermal state of the Moon and the physics of dynamo generation. The lunar sample with the oldest known paleomagnetic record is the 4.25 billion year old (Ga) troctolite 76535. Previous studies of unoriented subsamples of 76535 found evidence for a dynamo field with a paleointensity of several tens of microteslas. However, the lack of mutual subsample orientation prevented a demonstration that the magnetization was unidirectional, a key property of thermoremanent magnetization. Here we report further alternating field demagnetization on three mutually oriented subsamples of 76535, as well as new pressure remanent magnetization experiments to help rule out shock magnetization. We also describe new 40 Ar/ 39 Ar thermochronometry and cosmogenic neon measurements that better constrain the rock's thermal history. Although the rock is unbrecciated, unshocked, and slowly cooled, its demagnetization behavior is not ideal due to spurious remanence acquisition. Despite this limitation, all three subsamples record a high coercivity magnetization oriented in nearly the same direction, implying that they were magnetized by a unidirectional field on the Moon. We find no evidence for shock remanence, and our thermochronometry calculations show no significant reheating events since 4249 ± 12 million years ago (Ma). We infer a field paleointensity of approximately 20–40 μT, supporting the previous conclusion that a lunar dynamo existed at 4.25 Ga. The timing of this field supports an early dynamo powered by thermal or thermochemical core convection and/or a mechanical dynamo but marginally excludes a dynamo delayed by thermal blanketing from radiogenic element‐rich magma ocean cumulates. Key Points: Using mutually oriented subsamples of lunar troctolite 76535, we find further evidence for a dynamo on the Moon 4.25 Ga We find that the magnetizing field had a paleointensity of 20‐40 microteslas New 40 Ar/ 39 Ar thermochronometry measurements provide an improved sample age estimate of 4249 plus minus 12 Ma